Peran Zaid Bin Tsabit dalam Kodifikasi Al-Qur'an: Kajian Kritis Implikasi Kepastian Teks Nash terhadap Validitas Dalil-Dalil Hukum Keluarga - Ahmad Amin Febrianto; Ahmad Musonnif (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the importance of preserving the authenticity of the Qur’an as the primary source of Islamic teachings and law, which serves as the foundation for legal certainty within the Islamic Family Law system. Historical records show that the codification process of the Qur’an carried out by Zaid bin Tsabit during the caliphates of Abu Bakr and Uthman bin Affan played a crucial role in ensuring the integrity and uniformity of the revealed text, thereby having significant implications for the validity of Islamic legal arguments. This study aims to critically analyze the role of Zaid bin Tsabit in the Qur’anic codification process and its implications for the certainty of the textual basis (nash) in Islamic family law. Using a qualitative method with a historical-normative approach, this research combines chronological and normative analyses of primary sources such as the works of as-Suyuthi and az-Zarkasyi, as well as secondary sources in relevant academic literature. The findings indicate that the codification process of the Qur’an holds not only historical value but also juridical significance, as it ensures the authenticity of the text as the foundation of Islamic law. Therefore, integrating historical and normative aspects is essential to maintaining the authority of Islamic legal sources in the contemporary era.